DIFFERENT ANTIOXIDANT PROPERTIES FROM PADINA GYMNOSPORA MARINE ALGAE MEDIATED COPPER NANOPARTICLES - Shweta Mary Reddy, Dr.Abirami Arthanari (Chelonian Research Foundation, 2023)
Introduction : Padina gymnospora are a kind of marine brown algae that are well-known for their many bioactive components, including antioxidants. Our bodies produce free radicals on a regular basis, and their buildup can cause serious health issues and, ultimately, death. Numerous ailments, including heart attacks, are at a lower risk thanks to antioxidants. Because they are less volatile and more stable at high temperatures than synthetic antioxidants, more natural antioxidants are preferable. The inclusion of copper nanoparticles improves the antioxidant qualities that are already present. Aim: To synthesise Padina gymnospora mediated copper nanoparticles and to hence study their antioxidant properties. Materials and methods : Padina gymnospora samples are collected, cleaned with distilled water, dried, and powdered. The manufacturing of methanol extract begins with the powdering of crude oil extract, which is subsequently dried for a few hours. To identify the bioactive components from crude extract, further antioxidant assays (DPPH, Nitric oxide assay, SEM, EDX , light absorbance ) were conducted. Results: In tests using the DPPH and nitric oxide assays, it was shown that the seaweed Padina gymnospora's antioxidant ability increased with larger extract concentrations. Conclusion: In comparison to other earlier investigations, this study found that the ethanol extract of seaweed exhibited stronger antioxidant properties. Thus proving the antioxidant potential of Padina gymnospora as a more biotic alternative of an efficient antioxidant with enhanced properties exhibited by incorporating it in copper nanoparticles. Keywords:Padina Gymnospora-Marine algae-Copper nanoparticles-Antioxidant properties-Free radical scavenging-DPPH (2,2-diphenyl-1-picrylhydrazyl) assay- Nitric oxide assay- ethanolic crude extract- biotic